A method for preparing green methanol, green ethylene glycol, and reduced-carbon PET, and the catalyst used.

By using porous structures of copper-zinc-calcium-magnesium-aluminum and copper-zirconium-titanium-vana catalysts, combined with a side-by-side multi-tower and single/twin-tower design reactor, the existing catalyst conversion and selectivity are solved, and efficient carbon dioxide conversion and catalyst hydrolysis resistance are achieved.

CN119118790BActive Publication Date: 2025-04-15JIANGSU ZHONGLU TECH DEV CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411263121.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-04-15
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing catalysts for carbon dioxide to methanol have poor conversion and selectivity, and have defects that are not resistant to hydrolysis, which affects the service life of the catalyst.

Method used

The conversion rate and reaction selectivity of carbon dioxide are improved by a columnar and porous structure of copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst and copper-zirconium-titanium-vana deposition hydrogenation catalyst through a parallel multi-tower design first-stage fixed bed reactor and a single or double-tower design second-stage fixed bed reactor.

Benefits of technology

It significantly improves the conversion rate and reaction selectivity of carbon dioxide, extends the service life of the catalyst, and increases the production capacity of methanol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118790B_ABST
    Figure CN119118790B_ABST
Patent Text Reader

Abstract

The present invention relates to a preparation method for preparing green methanol, green ethylene glycol and carbon-reduced PET and a catalyst used therefor. The method captures and purifies a high-concentration carbon dioxide gas stream produced as a byproduct in a petroleum refining process into high-purity carbon dioxide, and then sequentially performs hydrogenation reactions in two-stage fixed-bed reactors to prepare green methanol. The first-stage fixed-bed reactor includes at least two parallel reaction towers equipped with copper-zinc-calcium-magnesium-aluminum hydrogenation catalysts, and the second-stage fixed-bed reactor includes at least one reaction tower equipped with a copper-zirconium-titanium-vanadium deposition-type hydrogenation catalyst. The green methanol can be used to prepare green ethylene glycol through an MTO process, ethylene oxidation, and ethylene oxide hydrolysis. The green ethylene glycol can be used to prepare environmentally friendly carbon-reduced polyester; in the esterification and polymerization process, by adding a specific esterification catalyst and a composite stabilizer, the performance of the environmentally friendly carbon-reduced polyester can be improved, making it comparable to the performance of the polyester product corresponding to the petrochemical method ethylene glycol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of petrochemical industry and polyester chemical technology, and specifically relates to a preparation method for green methanol, green ethylene glycol and carbon-reduced PET and a catalyst used therein. Background Art

[0002] The chemical fiber industry occupies a very important position in my country's national economy. my country is the world's largest producer of chemical fibers, accounting for more than 70% of the world's total chemical fiber output, of which polyethylene terephthalate fiber (a type of polyester fiber) accounts for more than 85% of the total chemical fiber output, and is the chemical fiber variety with the largest output and the widest application. Driven by the increasingly severe climate change, environmental protection concepts, and resource shortages, as well as the "dual carbon" vision, the circular economy and sustainable development model have gradually become an important direction and new economic growth point for the development of my country and even the world. Ethylene glycol is one of the main raw materials for the production of polyester. At present, it is mainly petroleum-based ethylene oxide hydration and coal chemical production of ethylene glycol. The development of industrial production technology for high-purity green ethylene glycol is one of the technical problems that urgently need to be solved in the polyester fiber industry's transformation to green and low-carbon.

[0003] In recent years, with the gradual depletion of fossil fuels such as oil, coal, and natural gas at home and abroad, modern chemical industry based on the consumption of fossil raw materials will inevitably undergo major changes, as greenhouse gases continue to increase and are destroyed; large amounts of carbon dioxide emissions are the biggest problem of modern life's atmospheric pollution to the earth, and are the direct cause of global warming and the extreme weather that has occurred in recent years.

[0004] With the development of new green, sustainable, biodegradable, carbon-reducing and environmentally friendly technologies, including the use of solar energy driven by the photovoltaic industry, wind power generation technology driven by lightweight and high-strength materials such as carbon fiber, large-capacity hydropower generation and tidal power generation technology under development, a series of new energy technologies have been provided, which have greatly reduced the consumption of fossil energy. The proportion of these green energy sources has further increased, providing strong support for the world to achieve a low-carbon economy.

[0005] Based on the urgent global demand for reducing carbon emissions and responding to climate change as well as my country's "dual carbon" goals, the capture and utilization of carbon resources emitted by industrial production is becoming an important means to reduce greenhouse gas emissions and achieve carbon neutrality. The development of industrial carbon capture technology can reduce emissions of carbon dioxide greenhouse gases through storage, chemical conversion and other means; however, the use of carbon dioxide storage is only a short-term control of greenhouse gas emissions and cannot fundamentally solve the problem of carbon dioxide emissions. The development of large-capacity carbon dioxide capture and purification PSA device technology can simply increase the carbon dioxide content and purify the quality of carbon dioxide, and the research on chemical conversion technology of carbon dioxide supported by green energy has now rapidly developed from laboratory research and development to the pilot scale-up and industrialization technology stage. Using carbon dioxide as a raw material and reacting with hydrogen to synthesize methanol can, on the one hand, capture CO in industrial waste gas. 2 , the concentrated carbon dioxide gas streams such as large-scale thermal power and refinery tail gas can be upgraded to a high purity level through simple purification technology to meet the quality requirements of carbon dioxide hydrogenation to produce methanol. On the other hand, various green energy sources can be used for electrolysis to produce hydrogen, providing completely green hydrogen resources. Carbon dioxide hydrogenation to methanol technology can provide a new and convenient idea for methanol production and energy storage, and has important promotion value. Another technology based on the current development of shale gas technology, the technology of mixing shale gas and carbon dioxide to hydrogenate to produce methanol has also been widely studied. At present, the technology of direct carbon dioxide hydrogenation to produce methanol has taken the lead in entering the field of industrial application.

[0006] In recent decades, many research institutions and companies at home and abroad have been continuously trying green methanol production technology, and the technical level has been continuously improving. The core of the technology of preparing methanol from carbon dioxide and hydrogen is the synthesis and selectivity of hydrogenation catalysts. The mainstream carbonyl hydrogenation catalysts include copper-zinc-aluminum oxides, copper-zinc carbonate compounds, etc., as well as new catalysts with a combination of multiple metal elements. However, in actual operation, although such catalysts have good catalytic efficiency and selectivity, they all have the defect of not being resistant to hydrolysis. The main reason is that zinc oxide and aluminum oxide combine with water to form hydroxides in the presence of water (a small amount of water generated during the reaction process) at high temperature, causing the loss of effective components of the catalyst.

[0007] Although the copper-zinc-gallium oxide catalyst described in US20140308597A1 replaces the aluminum element with gallium, the co-precipitated zinc oxide component still has the problem of a short catalyst period, mainly because the three element oxides fail to form a spatial structure co-combination and are a single oxide structure.

[0008] Patent US20190076828A1 records another combination, copper-zinc-magnesium co-precipitation after high-temperature treatment, which also has certain hydrolysis problems; many other foreign patents are research in this field. my country's research institutions, such as the Shanghai Institute of the Chinese Academy of Sciences and the Dalian Institute of Chemical Physics of the Chinese Academy of Sciences, have also conducted research on the synthesis of methanol from carbon dioxide and hydrogen, which are basically in the category of copper-zinc-aluminum combination catalysts. Their current research has not been able to break through the stage of industrial application.

[0009] At present, most catalysts for the production of methanol from carbon dioxide have poor conversion and selectivity. For this reason, some domestic and foreign companies and research institutions, such as Haldor Topse of Denmark, Kansai Electric Power and Mitsubishi Heavy Industries of Japan, Lurgi of Germany, and the Korea Institute of Science and Technology (KIST), are working on high-efficiency catalysts and corresponding technologies. The only industrially produced carbon dioxide hydrogenation to methanol project in the world is the ETL process technology developed by Carbon Recycling International (CRI) of Iceland. It uses electricity generated by geothermal power generation to electrolyze water to produce hydrogen, while recovering and extracting carbon dioxide from industrial tail gas, and then synthesizing green low-carbon methanol through CRI's proprietary ETL patented process. It uses a copper-zinc-aluminum-based hydrogenation catalyst. After special catalyst treatment technology, the reported operating life of the catalyst in the industrial device is 4-5 years, which has fully met the foundation for industrial operation.

[0010] Based on the above background, under the current conditions of vigorously advocating green manufacturing and sustainable development strategies in my country, especially the rapid development of photovoltaic power generation and wind power generation in my country, which have accounted for 15-20% of my country's total power generation, these green and clean energy can be used to produce electrolytic hydrogen, providing strong support for the technology of carbon dioxide to methanol. Regarding the design of industrial equipment for preparing methanol from carbon dioxide and hydrogen with high efficiency, good selectivity and hydrolysis resistance, methanol to prepare ethylene through MTO process, ethylene oxidation to prepare ethylene oxide, ethylene oxide hydrolysis to prepare industrial ethylene glycol raw materials, and green ethylene oxide and carbon dioxide to prepare ethylene carbonate, ethylene carbonate and green methanol alcoholysis to prepare green ethylene glycol + dimethyl carbonate and other system green manufacturing projects, it has become a new economic growth point in the current petrochemical industry. As a new technology of new quality productivity, it has a wide range of applications. Green ethylene glycol can be used in the polyester fiber industry to form a series of green carbon capture polyester fiber products, and green dimethyl carbonate can be used as a raw material for green polycarbonate high-end plastic products. Green methanol can be used to prepare a series of chemical products through ethylene and propylene. Summary of the invention

[0011] The purpose of the present invention is to provide a method for preparing green methanol, which is green and environmentally friendly and can significantly improve the conversion rate and reaction selectivity of carbon dioxide.

[0012] Another object of the present invention is to provide a catalyst for preparing green methanol. By using the catalyst, the conversion rate of carbon dioxide and the selectivity of the hydrogenation reaction can be significantly improved.

[0013] Another object of the present invention is to provide a method for preparing green ethylene glycol, which is green and environmentally friendly and can achieve low-carbon production.

[0014] Another object of the present invention is to provide a method for preparing carbon-reduced PET, which uses green ethylene glycol as one of the polymerization monomers to achieve carbon-reduced production of polyester, while ensuring that the performance of the polyester can basically achieve the performance level of polyester prepared by petrochemical ethylene glycol.

[0015] In order to achieve the above object, the technical solution adopted by the present invention is:

[0016] A method for preparing methanol, using carbon dioxide and hydrogen as raw materials to prepare methanol through hydrogenation reaction, wherein the hydrogenation reaction is sequentially carried out in two-stage fixed bed reactors, wherein the first-stage fixed bed reactor comprises at least two reaction towers arranged in parallel, and the second-stage fixed bed reactor comprises at least one reaction tower, wherein each reaction tower of the first-stage fixed bed reactor is filled with a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, and each reaction tower of the second-stage fixed bed reactor is filled with a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is columnar and has a porous structure, comprising a support carrier and active components; the active components comprise copper oxide, zinc oxide, calcium oxide, magnesium oxide and aluminum oxide; the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst is columnar and has a porous structure, comprising a support carrier, a nano-silicon dioxide carrier, and a porous deposition catalyst layer located on the surface of the nano-silicon dioxide carrier, wherein the porous deposition catalyst layer comprises copper oxide, zirconium oxide, titanium oxide and vanadium oxide; and the support carrier comprises graphite, activated carbon and a binder.

[0017] In the present invention, the parallel arrangement of reaction towers means that materials enter the reaction towers in parallel for reaction, each parallel arrangement of reaction towers processes materials at the same time, different materials react in different reaction towers at the same time, and the total reaction material amount is the sum of the material amounts of each reaction tower, rather than the materials reacting in each reaction tower in turn.

[0018] The present invention uses a new type of catalyst with a columnar and porous structure. At the same time, the first-stage methanol reactor adopts a parallel multi-tower design, and the second-stage methanol reactor adopts a single or double-tower design, which can promote the equilibrium reaction of synthesizing methanol to move in the opposite direction of the forward reaction, improve the conversion rate and selectivity of carbon dioxide when synthesizing methanol from carbon dioxide, and at the same time improve the production capacity of methanol. The use of staged reaction effectively increases the residence time of the mixed gas flow in the main reaction zone, and effectively improves the conversion rate of a single cycle reaction. The copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst has the ability to resist hydrolysis deactivation under the premise of having a good catalytic effect, is not affected by the water content in the reaction by-products, and its active components, namely the oxides in the porous deposition catalyst layer, are all insoluble in water and are stable oxidized deposits.

[0019] In some embodiments, the first-stage fixed bed reactor includes 2-6 reaction towers arranged in parallel.

[0020] Preferably, the first-stage fixed bed reactor comprises 3-5 reaction towers arranged in parallel.

[0021] In some embodiments, the second stage fixed bed reactor comprises 1-2 reaction towers.

[0022] Preferably, the second-stage fixed bed reactor comprises two reaction towers arranged in parallel.

[0023] In some embodiments, in the first-stage fixed bed reactor and the second-stage fixed bed reactor, each of the parallel reaction towers is provided with a nitrogen inlet and a nitrogen outlet.

[0024] In some embodiments, the method controls a reaction tower in the first-stage fixed bed reactor not to perform a hydrogenation reaction and serves as a spare tower, and also controls a reaction tower in the second-stage fixed bed reactor not to perform a hydrogenation reaction and serves as a spare tower; when the catalyst in a reaction tower performing a hydrogenation reaction in the first-stage fixed bed reactor or the second-stage fixed bed reactor reaches its service life, the reaction tower is switched to the spare tower; and the reaction tower is purged with nitrogen to regenerate the catalyst, and the temperature of the nitrogen is 300-400°C.

[0025] In some embodiments, in the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, the support carrier accounts for 40%-50% by weight, and the active component accounts for 50%-60% by weight.

[0026] In some embodiments, in the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, according to weight percentage, the copper oxide accounts for 30%-40% of the active component, the zinc oxide accounts for 23%-30% of the active component, the calcium oxide accounts for 4%-6% of the active component, the magnesium oxide accounts for 14%-18% of the active component, and the aluminum oxide accounts for 15%-20% of the active component.

[0027] Preferably, the copper oxide accounts for 32%-38% of the active component, the zinc oxide accounts for 24%-28% of the active component, the calcium oxide accounts for 4.2%-5.8% of the active component, the magnesium oxide accounts for 15%-17% of the active component, and the aluminum oxide accounts for 16.0%-19.0% of the active component.

[0028] More preferably, the copper oxide accounts for 34%-36% of the active component, the zinc oxide accounts for 25%-27% of the active component, the calcium oxide accounts for 4.5%-5.5% of the active component, the magnesium oxide accounts for 15.5%-16.5% of the active component, and the aluminum oxide accounts for 17.0%-18.0% of the active component.

[0029] In some embodiments, in the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, according to weight percentage, in the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, the supporting carrier accounts for 40%-50%, the nano-silica carrier accounts for 20%-25%, and the porous deposited catalyst layer accounts for 25%-40%.

[0030] In terms of weight percentage, the copper oxide accounts for 40%-50% of the porous deposited catalyst layer, the zirconium oxide accounts for 25%-35% of the porous deposited catalyst layer, the titanium oxide accounts for 10%-15% of the porous deposited catalyst layer, and the vanadium oxide accounts for 10%-15% of the porous deposited catalyst layer.

[0031] Preferably, the copper oxide accounts for 42%-48% of the porous deposited catalyst layer, the zirconium oxide accounts for 26%-34% of the porous deposited catalyst layer, the titanium oxide accounts for 10.8%-14.2% of the porous deposited catalyst layer, and the vanadium oxide accounts for 11.5%-13.5% of the porous deposited catalyst layer.

[0032] More preferably, the copper oxide accounts for 43.5%-46.5% of the porous deposited catalyst layer, the zirconium oxide accounts for 28%-32% of the porous deposited catalyst layer, the titanium oxide accounts for 11.5%-13.5% of the porous deposited catalyst layer, and the vanadium oxide accounts for 12%-13% of the porous deposited catalyst layer.

[0033] In some embodiments, the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst has a specific surface area of ​​125-150 m 2 / g.

[0034] In some embodiments, the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst has a length of 4-8 mm.

[0035] In some embodiments, the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst has a specific surface area of ​​80-100 m 2 / g.

[0036] In some embodiments, the copper-zirconium-titanium-vanadium deposition-type hydrogenation catalyst has a length of 4-8 mm.

[0037] In some embodiments, in the support carrier, by weight percentage, the graphite accounts for 30%-35%, the activated carbon accounts for 45%-55%, and the binder accounts for 15%-20%.

[0038] In some embodiments, the graphite has a particle size of 0.2-0.3 μm.

[0039] In some embodiments, the activated carbon is coconut shell charcoal powder.

[0040] In some embodiments, the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is prepared by a preparation method comprising the following steps: 1) mixing a water-soluble zinc salt, a water-soluble magnesium salt and a water-soluble aluminum salt in the form of a solution to obtain a mixed solution; dripping an aqueous sodium hydroxide solution into the mixed solution to obtain a coprecipitation sedimentation suspension; 2) simultaneously dripping an aqueous solution of a water-soluble copper salt, an aqueous solution of a water-soluble calcium salt and an aqueous sodium hydroxide solution into the coprecipitation sedimentation suspension; 3) adding an aqueous sodium bicarbonate solution to adjust the pH value of the reaction system; heating and aging; 4) placing the reaction system in a high-pressure reactor, and under heating and stirring conditions, high-pressure blasting, dehydration treatment, and redispersion in water to form a suspension; 5) dripping tetrabutyl silicate into the suspension; 6) filtering, adding graphite, activated carbon and a binder to the filter cake, and heating and shaping to obtain the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

[0041] The copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst of the present invention is a co-deposited porous nano multi-metal catalyst having excellent carbonyl hydrogenation catalytic activity and high selectivity. During high-pressure explosion, the high-pressure circulation pump is started to transport the high-temperature and high-pressure suspension to a specially designed high-pressure explosion nozzle, and the catalyst powder suspension that has completed the dehydration reaction is suddenly exploded from the high-pressure superheated condition to the normal pressure condition, and the submicron powder is exploded into nanometer powder, and the porous area rate of the powder is greatly improved.

[0042] In some embodiments, the water-soluble zinc salt, water-soluble magnesium salt, water-soluble aluminum salt, water-soluble copper salt and water-soluble calcium salt are respectively selected from sulfates, acetates or chlorides of the corresponding metal elements.

[0043] In some embodiments, in the mixed solution, the molar concentration of the water-soluble zinc salt is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0044] In some embodiments, in the mixed solution, the molar concentration of the water-soluble magnesium salt is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0045] In some embodiments, in the mixed solution, the molar concentration of the water-soluble aluminum salt is 1.0-3.0 mol / L, preferably 2.5 mol / L.

[0046] In some embodiments, the molar concentration of the sodium hydroxide aqueous solution is 1.0-3.0 mol / L, preferably 2.5 mol / L.

[0047] In some embodiments, the molar concentration of the aqueous solution of the water-soluble copper salt is 1.0-3.0 mol / L, preferably 3.0 mol / L.

[0048] In some embodiments, the molar concentration of the aqueous solution of the water-soluble calcium salt is 1.0-3.0 mol / L, preferably 0.5 mol / L.

[0049] In some embodiments, the molar concentration of the sodium bicarbonate aqueous solution is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0050] In some embodiments, the dropping in steps 1) and 2) is performed at 70-80°C.

[0051] In some embodiments, the dropping in steps 1) and 2) is performed at a pH of 9.5-10.5.

[0052] In some embodiments, in step 3), the pH value of the system after adjustment is 9.5-10.5, preferably 10.0.

[0053] In some embodiments, the high pressure blasting in step 4) is performed by a high pressure blasting nozzle.

[0054] In some embodiments, in step 5), the dropping of tetrabutyl silicate is performed at 70-80° C. for 6-8 hours.

[0055] In some embodiments, the tetrabutyl silicate accounts for 100-150 ppm by mass of the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

[0056] In some embodiments, in step 6), the temperature of the heating and setting is 320-350°C.

[0057] In some embodiments, the copper-zirconium-titanium-vanadium deposition-type hydrogenation catalyst is prepared by a preparation method comprising the following steps: 1) synchronously titrating an aqueous solution of a water-soluble copper salt, a tetraalkyl zirconium, a tetraalkyl titanate, an aqueous solution of sodium metavanadate, an aqueous solution of sodium hydroxide, and an aqueous solution of sodium carbonate on a nano-silica carrier, and after the reaction, a porous deposition catalyst layer is formed on the nano-silica carrier; the alkyl group is a C1-6 alkyl group; 2) filtering, adding graphite, activated carbon and a binder to the filter cake, and heating it to obtain the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

[0058] In some embodiments, the water-soluble copper salt is selected from one or both of copper sulfate and copper chloride.

[0059] In some embodiments, the tetraalkyl zirconium is tetraethyl zirconium.

[0060] In some embodiments, the tetraalkyl titanate is tetraisopropyl titanate.

[0061] In some embodiments, the molar concentration of the aqueous solution of the water-soluble copper salt is 1.0-3.0 mol / L, preferably 3.0 mol / L.

[0062] In some embodiments, the molar concentration of the sodium metavanadate aqueous solution is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0063] In some embodiments, the molar concentration of the sodium hydroxide aqueous solution is 1.0-3.0 mol / L, preferably 2.5 mol / L.

[0064] In some embodiments, the molar concentration of the sodium bicarbonate aqueous solution is 1.0-3.0 mol / L, preferably 2.0 mol / L.

[0065] In some embodiments, in step 1), the titration is performed at a pH of 9-11.

[0066] In some embodiments, in step 2), the heating treatment is performed at a temperature of 50-600° C. and for a time of 16-24 hours.

[0067] In some embodiments, each reaction tower of the first-stage fixed bed reactor and the second-stage fixed bed reactor includes an inner chamber and an outer chamber; the inner chamber includes multiple layers of horizontally arranged tower plates; two adjacent tower plates are staggered; the outer chamber is designed as a circular tower design, and multiple groups of equalizing plates are designed at the top, middle and bottom of the outer chamber; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is filled between the inner chamber and the equalizing plates of the outer chamber; and a filter is provided at the bottom of the outer chamber.

[0068] In the present invention, the aforementioned staggered design of two adjacent tower trays means that the projections of the two tower trays on the horizontal plane partially overlap. For example, an upper tower tray is fixed on one side of the inner chamber, and its horizontal length is smaller than the diameter of the inner chamber. An adjacent lower tower tray is fixed on the other side of the inner chamber, and its horizontal length is also smaller than the diameter of the inner chamber. Moreover, the projections of the two on the horizontal plane partially overlap, so that the airflow can flow between the two adjacent tower trays, thereby extending the residence time of the airflow.

[0069] In some embodiments, the effective volumes of the inner chamber and the outer chamber are the same.

[0070] In some embodiments, the residence time of the reaction gas in the inner chamber and the outer chamber is the same, so as to ensure the stability of the entire reaction in the two-stage fixed bed reactor.

[0071] In some embodiments, the residence time of the raw gas in the first-stage fixed bed reactor is 275-350 s, preferably 290-340 s, and more preferably 300-330 s.

[0072] In some embodiments, after the hydrogenation reaction in the first stage fixed bed reactor is completed, the conversion rate of carbon dioxide is 64.0%-75.8%, preferably 66.5%-75.8%, and more preferably 70.5%-75.8%.

[0073] In some embodiments, the volume of each reaction tower of the first stage fixed bed reactor is 135-150m 3 The volume of the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is 75-90m 3 .

[0074] In some embodiments, the volume of each reaction tower of the second stage fixed bed reactor is 135-150m 3 The volume of the copper-zirconium-titanium-vanadium deposited hydrogenation catalyst is 75-90m 3 .

[0075] In some embodiments, the residence time of the reaction system in the second-stage fixed bed reactor is 75-100 s.

[0076] In some embodiments, in the second-stage fixed bed reactor, the effective self-circulation ratio of the reaction system is 3.5-6.0.

[0077] The aforementioned effective self-circulation ratio refers to the ratio of the total mass of the circulating airflow to the mass of the introduced material re-added from the outside.

[0078] In some embodiments, after the hydrogenation reaction in the second stage fixed bed reactor is completed, the cumulative conversion rate of carbon dioxide is 92.4%-95.5%.

[0079] In some embodiments, the temperature of the first-stage fixed bed reactor is 150-350° C., and the pressure is 5.0-20.0 MPa.

[0080] Preferably, the temperature of the first-stage fixed bed reactor is 180-300° C., and the pressure is 7.5-15 MPa.

[0081] More preferably, the temperature of the first-stage fixed bed reactor is 260-280° C., and the pressure is 8.0-10 MPa.

[0082] In some embodiments, the temperature of the second-stage fixed bed reactor is 120-240° C., and the pressure is 10.0-20.0 MPa.

[0083] Preferably, the temperature of the second-stage fixed bed reactor is 150-200° C., and the pressure is 12.5-17.5 MPa.

[0084] More preferably, the temperature of the second-stage fixed bed reactor is 160-180° C., and the pressure is 14.0-15.0 MPa.

[0085] In some embodiments, the carbon dioxide is derived from a byproduct of a petroleum refining process.

[0086] Preferably, the volume content of carbon dioxide in the byproduct of the petroleum refining process is 80%-90%. Carbon dioxide also contains a certain amount of low molecular weight alkanes, low molecular weight olefins, water, organic low molecular weight gases containing sulfur, nitrogen, phosphorus and other impurities.

[0087] In some embodiments, the method further comprises the steps of filtering, washing with water, washing with ammonia water, removing suspended solids, and treating with a pressure swing adsorption (PSA) device for the by-products of the petroleum refining process. After these steps, the volume content of carbon dioxide is 98.0%-99.5%.

[0088] In some embodiments, after the carbon dioxide and hydrogen are mixed and pressurized, they enter the first-stage fixed bed reactor from the bottom for hydrogenation reaction. The gas flow after the reaction flows out from the bottom of the first-stage fixed bed reactor, enters the condenser for condensation, and enters the methanol phase separation device for phase separation after decompression.

[0089] In some embodiments, the molar ratio of carbon dioxide to hydrogen is 1:3-4.5.

[0090] In some embodiments, the gas flow at the top of the methanol phase separation device (mainly mixed components such as unreacted carbon dioxide, hydrogen, methane, carbon monoxide, water, etc.) and the added hydrogen are mixed and pressurized, and then enter the second-stage fixed bed reactor from the lower middle part. The mixed gas flow undergoes a hydrogenation reaction in the second-stage fixed bed reactor, and the liquid components after the reaction (methanol obtained by the reaction and components with heavier molecular weight) flow out from the bottom of the second-stage fixed bed reactor and enter the first methanol phase separation device for phase separation.

[0091] In some embodiments, the amount of the supplemental hydrogen accounts for 4% to 8% of the amount of hydrogen entering the first-stage fixed bed reactor.

[0092] In some embodiments, the tail gas at the top of the second-stage fixed bed reactor is introduced into a pressure swing adsorption (PSA) device after decompression treatment to adsorb hydrogen, and then desorb and recover hydrogen.

[0093] In some embodiments, the recovered hydrogen is used as the source of the additional hydrogen entering the second stage fixed bed reactor. In the present invention, the unreacted mixed gas at the top of the methanol phase separation device shared by the first and second stage methanol reactors is introduced into the second stage methanol reactor after being pressurized by a compressor, and a large-scale circulation reaction mode is adopted.

[0094] In some embodiments, the tail gas after hydrogen adsorption contains a small amount of carbon dioxide, methane, ethane, formaldehyde, acetaldehyde, trace hydrogen and other components and is sent to a tail gas incineration device for treatment and discharge.

[0095] In some embodiments, the liquid crude methanol separated by the methanol phase separation device is subjected to two-stage distillation separation, and the pressure of the second stage distillation is higher than the pressure of the first stage distillation.

[0096] For the two-stage distillation separation system, the first stage distillation adopts low-pressure distillation to transport crude methanol to the bottom of the first-stage distillation tower, and methanol is extracted from the top of the distillation tower and transported to the refined methanol product tank through cooling and reflux. The heavy components at the bottom of the low-pressure distillation tower mainly contain 50%-60% methanol, and other high-boiling point by-products, which are transported to the middle of the second-stage methanol distillation tower through a circulation pump, and then high-quality methanol is further extracted from the top of the tower by distillation, and transported to the refined methanol product tank after cooling; the high-boiling point components extracted from the bottom are transported to the fusel oil storage tank as fusel oil for further processing.

[0097] The present invention also provides a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst used in the above method.

[0098] The present invention also provides a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst used in the above method.

[0099] The present invention also provides a method for preparing ethylene glycol, comprising the steps of preparing ethylene from methanol via MTO (Methanol to Olefins) technology, preparing ethylene oxide by oxidation of ethylene, and preparing ethylene glycol by hydrolysis of ethylene oxide; the preparation method also includes the step of preparing methanol by the aforementioned method for preparing methanol of the present invention.

[0100] The ethylene glycol prepared by the method has good quality and can meet the requirements of conventional polyester esterification and polymerization reactions, thereby obtaining green carbon-reduced polyester that meets the requirements of fiber spinning.

[0101] The present invention also provides a method for preparing polyethylene terephthalate, comprising the steps of sequentially subjecting terephthalic acid and ethylene glycol to a first esterification, a second esterification, a first prepolymerization, a second prepolymerization and a final polymerization; the ethylene glycol is the ethylene glycol prepared according to the aforementioned method for preparing ethylene glycol of the present invention; the preparation method further comprises the step of adding an esterification catalyst and a composite stabilizer to terephthalic acid and ethylene glycol before the first esterification step; the esterification catalyst is selected from a combination of one or more of zinc acetate, manganese acetate, potassium acetate, sodium acetate, cobalt acetate, calcium acetate and lithium acetate; the composite stabilizer comprises an amine stabilizer, sodium bisulfite and a phosphorus stabilizer.

[0102] Using terephthalic acid PTA and industrial by-product CO 2 The ethylene glycol raw material prepared by airflow can be used to prepare environmentally friendly carbon-reducing polyester through slurry preparation, esterification reaction and polymerization reaction. In the esterification and polymerization process, according to the types and content levels of by-products of the ethylene glycol raw material, the present invention has developed an esterification catalyst and a composite stabilizer, which can realize the preparation of green carbon-reducing polyester and ensure that its performance can basically achieve the level of polyester synthesized by ethylene glycol produced by traditional petrochemical methods.

[0103] In some embodiments, the esterification catalyst is a mixture of zinc acetate, manganese acetate and lithium acetate.

[0104] In some embodiments, the mass of the esterification catalyst accounts for 100-200 ppm of the mass of the polyethylene terephthalate.

[0105] In some embodiments, the amine stabilizer is selected from a combination of one or more of triethanolamine, triethylamine, diethylpropylamine, tert-butylamine, and diisopropylamine.

[0106] In some embodiments, the phosphorus-based stabilizer is selected from a combination of one or more of triphenyl phosphite, triphenyl phosphite, triethyl phosphate, trimethyl phosphate, and phosphoric acid.

[0107] In some embodiments, in the mixture, the molar ratio of zinc acetate, manganese acetate and lithium acetate is 1:0.3-0.6:0.5-0.75; preferably 1:0.35-0.50:0.55-0.70, and more preferably 1:0.40-0.45:0.55-0.60.

[0108] In some embodiments, the mass of the amine stabilizer accounts for 35-50 ppm of the mass of the polyethylene terephthalate.

[0109] In some embodiments, the mass of the sodium bisulfite accounts for 15-20 ppm of the mass of the polyethylene terephthalate.

[0110] In some embodiments, the mass of the phosphorus-based stabilizer accounts for 125-150 ppm of the mass of the polyethylene terephthalate.

[0111] In some embodiments, the preparation method further comprises the step of adding a titanium-based multi-metal catalyst as a polymerization catalyst in the second esterification step.

[0112] Further, the titanium-based multi-metal catalyst can be a nano-supported solid-phase titanium-based multi-metal catalyst in CN117567730A, the full text of which is incorporated by reference into the present invention. By using this catalyst, the influence of low molecular byproducts in green EG on antimony catalysts such as ethylene glycol antimony can be avoided. Such low molecular byproducts have reducibility and can react with antimony catalysts such as ethylene glycol antimony to generate antimony precipitation, which will reduce the catalytic activity of the catalyst and cause the product hue to deteriorate, and the L value is greatly reduced. The aforementioned titanium-based multi-metal catalyst is a surface-deposited solid-phase ultrafine nano-porous catalyst, which is coated with surface silicone ester, has good dispersibility and maintains excellent stability during the polymerization process, wherein the titanium element is deposited on the carrier surface in an amorphous state of titanium dioxide, and is firmly combined with the carrier, and a part of the titanium dioxide is bonded to the carrier surface, so it has a mild catalytic effect and will not form a single substance precipitation of titanium element. Therefore, the slice hue is greatly improved, the L value is greatly improved, and the product quality is also significantly better than the product using antimony catalyst. Titanium-based multi-metal catalysts are environmentally friendly green catalysts that can further improve the green environmental protection level of polyester products.

[0113] In some embodiments, the preparation method further includes the step of adding a solid-phase tracer in the second esterification step; the solid-phase tracer is selected from a combination of one or more of hydrophilic nano-silica, γ-nano-aluminum oxide, nano-barium sulfate powder, sub-nano-scale composite calcium carbonate-magnesium carbonate, sub-nano-scale attapulgite powder and multi-element light metal zeolite nano-powder.

[0114] Although the green ethylene glycol of the present invention is derived from industrial waste gas CO 2Methanol is captured and prepared, and ethylene oxide is prepared to green ethylene glycol through the MTO process. However, in the process of its application, it is currently impossible to use chemical composition to indicate the source of the green ethylene glycol. Therefore, in order to accurately indicate the unique source of green carbon capture ethylene glycol in the production and consumption links, the present invention uses a tracer, that is, a chemically inert substance in the esterification, polymerization reaction process, and spinning production and consumption process. Within the content range of 20 to 300 ppm, its content and components can be accurately detected by instruments or chemical methods.

[0115] For the above-mentioned solid-phase tracers, an effective detection method is to determine the content of the marker through elemental emission spectroscopy. For further confirmation, the presence of the nano-marker can be confirmed by taking photos using a scanning electron microscope.

[0116] In some embodiments, the preparation method further includes the step of adding a liquid phase tracer to terephthalic acid and ethylene glycol before performing the first esterification step; the liquid phase tracer is selected from a combination of one or more of isophthalic acid, phthalic acid, trimellitic acid, pyromellitic acid, cyclohexanedicarboxylic acid, 2,2,4,4-tetramethylcyclobutanedicarboxylic acid, pentaerythritol, neopentyl glycol, 1,2-dibutanol, 2,2,4,4-tetramethylcyclobutane dimethanol and 1,4-cyclohexanedimethanol.

[0117] For the above-mentioned liquid phase tracer, a polymerized monomer with an obvious nuclear magnetic resonance effect is used, which can show the absorption peak of its structural characteristics in the nuclear magnetic resonance area. It can be used as a monomer polymerized in the macromolecular segment, and its content is 50-300ppm. It can show obvious absorption characteristic peaks in nuclear magnetic resonance, and the liquid phase marker can be combined with the solid phase marker. Through batch and content adjustment, the entire life cycle of the green ethylene glycol-based fiber can be comprehensively tracked and confirmed.

[0118] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0119] The present invention uses a new type of catalyst with a columnar porous structure. At the same time, the first-stage methanol reactor adopts a parallel multi-tower design, and the second-stage methanol reactor adopts a single or double-tower design, which can promote the equilibrium reaction of synthesizing methanol to move in the opposite direction of the forward reaction, improve the conversion rate and selectivity of carbon dioxide when synthesizing methanol from carbon dioxide, and at the same time improve the production capacity of methanol. The staged reaction effectively increases the residence time of the mixed gas flow in the main reaction zone, and effectively improves the conversion rate of a single cycle reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0120] Figure 1 Schematic diagram of the structure of the methanol synthesis and distillation device used in the examples;

[0121] Figure 2Schematic diagram of the structure of the first stage fixed bed reactor used in the embodiment;

[0122] Among them, 1-first stage fixed bed reactor, 2-second stage fixed bed reactor, 3-reaction tower, 4-methanol phase separation device, 5-pressure swing adsorption PSA device, 6-crude methanol storage tank, 7-low-pressure methanol distillation tower, 9-medium-pressure methanol distillation tower, 10-inner chamber, 11-outer chamber, 12-tower tray, 13-homogenizing tray, aH 2 , b-CO 2 , cN 2 , d-tail gas, e-crude methanol + CO 2 +H 2 , f-refined methanol, g-fusel oil. DETAILED DESCRIPTION

[0123] In the traditional synthesis of methanol through carbon dioxide hydrogenation reaction, for the high-pressure and high-temperature hydrogenation reactor, due to the limitations of materials and reaction temperature (pressure resistance 15.0Mpa, temperature 350℃), the volume of a single reactor structure should not be too large (generally based on material balance, heat calculation and safety requirements, the total volume of a 100,000-ton methanol reactor is 50-100m 3 ), so the airflow stays in the reactor for a short time. The existing methanol reactor design (the full volume of a 100,000 ton methanol reactor is approximately equal to 50m 3 ) adopts a large-volume self-circulation design for exhaust gas, which consumes a lot of energy, the residence time of the mixed gas in the catalyst area is short, the degree of single-pass reaction is low, and the overall conversion rate of carbon dioxide is limited and very low.

[0124] In this patent, the first-stage methanol reactor adopts a parallel multi-tower single-cycle regenerable catalyst design technology, the second stage adopts a single / double-tower design, and the second-stage methanol reactor adopts a high-rate self-circulating hydrogenation reaction. The reaction products at the bottom of the two-stage methanol reactor are introduced into a common methanol phase separation device after heat exchange and cooling. The crude methanol and the unreacted mixed gas are separated in the methanol phase separation device, and the bottom crude methanol is introduced into the crude methanol intermediate tank. The unreacted gas at the top is compressed by a compressor and transported to the bottom inner chamber of the secondary methanol reactor, so that methanol preparation is efficiently completed at a high rate (3.6 to 6.0 times the circulation ratio).

[0125] The first-stage methanol reactor adopts a multi-tower design (for example, it can be 3-6 independent reaction towers, one of which is used as a spare tower) to meet the needs of large capacity, single-cycle continuous operation, online regeneration or regular replacement of catalysts. Under operating conditions, each methanol reaction tower has an independent effective production capacity of 30,000-100,000 tons / year, and adopts an operating process mode of multiple towers with one tower as spare. The actual operating capacity is 100,000-500,000 tons / year, and more methanol reaction towers can be designed to increase the production capacity.

[0126] The second-stage methanol reactor designed by this patent can adopt a parallel double-tower structure design as needed. In order to ensure the long-term operation of the device, the secondary methanol reactor adopts a one-in-one standby mode, which can easily complete the catalyst regeneration and replacement. Since the air flow source of the second-stage methanol reactor contains a certain amount of water, it is necessary to develop a catalyst with hydrolysis resistance. The copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst (hydrolysis-resistant deactivation) does not contain oxide components that react with water. The catalyst reaction temperature and pressure are different from those of the first-stage methanol reactor. The hydrogenation reaction can be completed at a lower temperature and a higher pressure, which greatly improves the operation cycle of the device.

[0127] One of the innovative points of the present invention is the use of a hydrolysis-resistant copper-zirconium-titanium-vanadium deposition-type oxide hydrogenation catalyst in a secondary methanol reactor, which has the effects of hydrolysis resistance and resistance to hydrolysis deactivation. The catalyst is developed and designed based on the characteristics of the reaction gas phase components after the reaction in the primary hydrogenation reactor is completed and separated by a methanol phase separation device. The reaction temperature and pressure of the catalyst are different from those of the first-stage methanol reactor. The hydrogenation reaction can be completed at a lower temperature and a higher pressure, and the mixed phase separation is completed by gas-liquid separation. The crude methanol and high-boiling point by-products are introduced into the crude methanol storage tank from the bottom, and the gas phase part is led out from the top and sent to the third-stage methanol reactor. Since the second-stage reactor uses the aforementioned hydrolysis-resistant hydrogenation catalyst, the carbon dioxide that failed to be completed in the first-stage methanol reactor is further reacted with hydrogen, and the degree of carbon dioxide hydrogenation reaction is further improved.

[0128] One of the innovations of the present invention is that the first-stage methanol reactor of the main reaction device has a raw material inlet of pure carbon dioxide and hydrogen mixed gas. Compared with the single-stage methanol reactor, the unreacted recycled gas is injected into the mixed gas inlet, eliminating the influence of reaction by-products on the catalyst activity, greatly extending the service life of the hydrogenation catalyst, and improving the efficiency of the main reaction of the first-stage methanol reactor. In particular, the influence of moisture in the by-products on the catalyst.

[0129] One of the innovative points of the present invention is the specific structural setting of the two-stage fixed bed reactor. Specifically, carbon dioxide gas and hydrogen are compressed and mixed and then injected into the system from the bottom of the inner chamber of the first-stage fixed bed reactor. The inner chamber of the reactor is designed as a multi-layer tray design. For each stage of the tray, the reaction mixed gas enters from a corner of the bottom of the tray, flows horizontally along the tray, and enters the upper tray from the upper channel diagonally opposite the bottom corner, and circulates to the top of the inner chamber. This design effectively improves the contact residence time of the mixed gas and the catalyst, and improves the reaction uniformity and reaction efficiency. The outer chamber is designed as a tower design. After the mixed gas reacts in the inner chamber, it is collected at the top of the reactor and then enters the outer chamber for reaction. The mixed gas flow in the outer chamber flows from top to bottom to the bottom of the reactor, and after being collected, it is introduced into the first methanol phase separation device through heat exchange and cooling. Multiple groups of homogenizing disks are designed at the top, middle and bottom of the outer chamber, and catalyst particles are filled between the homogenizing disks. Each homogenizing disk first collects gas, and then guides it to the next layer through the homogenizing design channel to ensure that the mixed gas flow passes through multiple catalyst layers in the tower body evenly. A filter screen is designed at the bottom of the outer chamber to prevent catalyst particles from entering the bottom outlet.

[0130] One of the innovations of the present invention is that the first-stage methanol reactor adopts a multi-tower design. Each reaction tower can be isolated separately and equipped with a high-temperature dry refined nitrogen inlet and outlet. After the single-tower catalyst reaches the end of its service life, it can be switched to the standby tower online and then purged with high-temperature (300-400°C) nitrogen. On the one hand, the moisture adsorbed by the catalyst can be dried. On the other hand, the viscous byproduct coke such as paraffin formed during the reaction process can be stripped from the surface of the catalyst columnar particles to achieve catalyst regeneration, effectively extend the service life of the catalyst, and maintain efficient reaction through regular regeneration operations.

[0131] Unlike ethylene glycol EG prepared by petrochemical ethylene engineering, the green ethylene glycol prepared by this patent has different impurities and byproducts in its components, especially in the types and contents of low molecular aldehydes and organic acids. Specifically, the ethylene glycol prepared by the present invention has a higher acetaldehyde content, a lower 1,4-dioxane content, a slightly higher low molecular carboxylic acid content than petrochemical ethylene glycol, and a slightly lower ultraviolet light transmittance at 220nm and 250nm than petrochemical ethylene glycol. This will lead to a decrease in the hue L value of the PET product, a lower a value, and a higher b value during the esterification and polymerization reaction process when the subsequent polymerization is used to synthesize PET. And its esterification reaction rate is significantly lower than that of petrochemical ethylene glycol. Under the same esterification conditions, the esterification rate of the green EG of the present invention in the first esterification kettle decreases by 3%-5%, and the esterification rate of the second esterification kettle decreases by 2.2%-4.0%.

[0132] In this regard, one of the innovative points of the present invention is to add an esterification catalyst to ensure that the esterification reaction proceeds smoothly. The manganese element in the manganese acetate in the esterification catalyst has reducing properties and can react with metal compounds with oxidizing properties during the reaction process, and can also react with the oxidant component in the reaction system, thereby avoiding the deactivation of the effective active center components of antimony-based and titanium-based catalysts, thereby ensuring the good esterification reaction state of the new green ethylene glycol. In addition, during polymerization, an alcohol amine stabilizer with a complexing function is combined with sodium bisulfite to form a composite stabilizer with a phosphorus stabilizer. Among them, the alcohol amine stabilizer can effectively complex and seal the heavy metal element ions and reducing low-molecular organic impurities in the green ethylene glycol, and sodium bisulfite can seal the active aldehyde and ketone by-products, thereby reducing the level of side reactions produced by this component, and the phosphorus stabilizer can control the thermal degradation reaction during the esterification and polymerization reactions.

[0133] The patented technology for preparing methanol by hydrogenation of carbon dioxide adopts a parallel multi-tower (3 to 6 towers) regenerable catalyst design technology for the first-stage methanol reactor, and a single / double-tower design for the second-stage methanol reactor. The first and second-stage methanol reactors share a methanol phase separation device. Liquid crude methanol is discharged from the bottom of the methanol phase separation device and sent to the crude methanol intermediate tank, and unreacted carbon dioxide, hydrogen and by-product mixed gas is discharged from the top. The mixed gas is pressurized by a compressor and introduced into the second-stage methanol reactor. The second-stage methanol reactor is designed to be self-circulating, and high-rate (3.6 to 6.0 circulation multiples) self-circulating to efficiently complete methanol preparation. The newly designed large-capacity carbon dioxide hydrogenation reactor technology uses high-strength titanium plates as materials to process the methanol reactor, which effectively increases the full volume of the first-stage methanol reactor and greatly increases the residence time of the carbon dioxide and hydrogen mixed gas in the fixed bed of the methanol reactor. The unique inner chamber gas phase flow channel design and outer chamber homogenization and diversion design make the reaction more uniform. The first-stage methanol reactor does not use tail gas circulation to improve the conversion rate of the primary reaction. The high-proportion self-circulation technology of the second-stage methanol reactor further optimizes the process flow. With more reasonable process flow technology, the catalyst service life is extended, and the conversion efficiency of carbon dioxide hydrogenation to methanol is improved. The use of catalysts with different components also further improves the operating stability of the device from the material reaction level.

[0134] The above scheme is further described below in conjunction with specific examples; it should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions used in the examples can be further adjusted according to specific requirements, and the unspecified implementation conditions are usually the conditions in conventional experiments. Unless otherwise specified in the following examples, all raw materials are purchased from commercial sources or prepared by conventional methods in the art.

[0135] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0136] The present invention is further described below in conjunction with the accompanying drawings and preferred embodiments of the present invention. The orientations and positional relationships described in the present invention are only for the convenience of describing the invention and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, only have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention.

[0137] like Figure 1-2 As shown, the device system for preparing methanol includes Figure 1 A two-stage fixed bed reactor for synthesizing methanol, wherein the first stage fixed bed reactor is enlarged as follows Figure 2 The first stage fixed bed reactor 1 is filled with a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, and the second stage fixed bed reactor 2 is filled with a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst.

[0138] like Figure 1-2 As shown, the first-stage fixed bed reactor 1 and the second-stage fixed bed reactor 2 both include an inner chamber 10 and an outer chamber 11; the inner chamber 10 includes multiple layers of horizontally arranged tower plates 12; two adjacent tower plates 12 are staggered; the outer chamber 11 is designed as a circular tower design, and multiple groups of equalizing plates 13 are designed at the top, middle and bottom of the outer chamber 11; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is filled between the inner chamber 10 and the equalizing plates 13 of the outer chamber 11; and a filter screen (not shown in the figure) is arranged at the bottom of the outer chamber 11.

[0139] like Figure 1As shown, after carbon dioxide and hydrogen are mixed and pressurized, they enter the first-stage fixed bed reactor 1 from the bottom for hydrogenation reaction, and the gas flow after the reaction flows out from the bottom of the first-stage fixed bed reactor 1, enters the condenser for condensation, and enters the methanol phase separation device 4 for phase separation after decompression. After the gas flow at the top of the methanol phase separation device 4 and the added hydrogen are mixed and pressurized, they enter the second-stage fixed bed reactor 2 from the middle and lower part, and the mixed gas flow undergoes hydrogenation reaction in the second-stage fixed bed reactor 2. The liquid component after the reaction flows out from the bottom of the second-stage fixed bed reactor 2 and enters the methanol phase separation device 4 for phase separation. The tail gas at the top of the second-stage fixed bed reactor 2 is introduced into the pressure swing adsorption PSA device 5 after decompression treatment, and hydrogen is adsorbed, desorbed, and hydrogen is recovered. The recovered hydrogen is used as the source of the additional hydrogen entering the second-stage fixed bed reactor 2. The liquefied liquid crude methanol generated by the two-stage fixed bed reactor and separated by the methanol phase separation device 4 can be introduced into the crude methanol storage tank 6 for storage.

[0140] like Figure 1 As shown, the liquid crude methanol separated by the methanol phase separation device 4 is subjected to two-stage distillation separation, and the pressure of the second stage distillation is higher than that of the first stage distillation. For the two-stage distillation separation system, the first stage distillation adopts low-pressure distillation, and the crude methanol is transported to the bottom of the low-pressure methanol distillation tower 7, and the methanol is extracted from the top of the distillation tower and transported to the refined methanol storage tank 10 after cooling and reflux. The heavy components at the bottom of the low-pressure methanol distillation tower 7 are mainly 50%-60% methanol, and other high-boiling point by-products, which are transported to the middle of the medium-pressure methanol distillation tower 9 through a circulation pump, and then high-quality methanol is further extracted from the top of the tower through distillation, and transported to the refined methanol storage tank after cooling; the high-boiling point components extracted from the bottom are transported to the fusel oil storage tank as fusel oil for further processing.

[0141] Preparation Example 1

[0142] This preparation example provides a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, and its preparation method is as follows:

[0143] First, prepare 1.0M aqueous solution of copper sulfate, zinc sulfate, calcium chloride, magnesium sulfate and aluminum sulfate, filter with quantitative filter paper and set aside. Prepare 1.0M sodium hydroxide aqueous solution and 0.5M sodium bicarbonate aqueous solution. Mix the zinc sulfate aqueous solution, magnesium sulfate aqueous solution and aluminum sulfate aqueous solution at a molar ratio of 1.0:1.0:0.75, and then add the above sodium hydroxide aqueous solution to the mixed solution under stirring for 4.0 hours, control the molar ratio of metal ions to hydroxide to meet the stoichiometric ratio, and prepare a coprecipitation suspension. Control the temperature of the system to 70°C during the addition, and continue to stabilize for 2.0 hours after the addition is completed.

[0144] The copper sulfate aqueous solution and the calcium chloride aqueous solution are added to the above-mentioned coprecipitation suspension in a molar ratio of 1.5:1.8, and the sodium hydroxide aqueous solution prepared above is added simultaneously in a stoichiometric ratio. The dropping time is controlled to be 4 hours, and the pH value of the system is controlled to be about 10 during the dropping process. After the dropwise addition is completed, the pH value of the suspension is adjusted to 10.0 with an aqueous sodium bicarbonate solution. The suspension is heated to 90°C and stabilized for 1.0 hours. The suspension is then transferred to a 2.5MPa pressure-resistant stainless steel reactor, heated to 220°C under high-speed stirring conditions, and stirred for 5.0 hours, and then the high-pressure circulation pump is started to transport the suspension to a specially designed high-pressure blasting nozzle. The suspension is first dehydrated in the high-pressure blasting nozzle under high-pressure overheating conditions, and then suddenly exploded to normal pressure conditions. In this process, the submicron powder in the suspension is exploded into nano-scale powder, and the porosity and specific surface area of ​​the powder are greatly improved.

[0145] The nano powder after blasting is partially dehydrated, and after washing away the soluble components with distilled water, a water suspension with a concentration of 10% is formed under stirring conditions. Tetrabutyl silicate accounting for 150ppm of the powder mass is added to the water suspension at a temperature of 80°C, and the dropping time is controlled to be 6 hours. After the dropping is completed, it is aged for 2.0 hours. The water is filtered to remove the water, and submicron graphite, coconut shell carbon powder, and adhesive (the mass ratio of the three is 3:5:2) are added to the filter cake as a supporting carrier to prepare a columnar porous granular material, which is dried and shaped at 320°C to obtain a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

[0146] The specific surface area of ​​the catalyst is 125 m 2 / g, cylindrical, and the length of the column is 4.0mm.

[0147] In the catalyst, the support carrier accounts for 40wt%, the active component accounts for 60wt%, and the active component, according to mass percentage, accounts for 35.0% of copper oxide, 26.0% of zinc oxide, 4.2% of calcium oxide, 16.8% of magnesium oxide, and 18.0% of aluminum oxide.

[0148] Preparation Example 2

[0149] This preparation example provides a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst, and its preparation method is as follows:

[0150] Nano-silica was used as a carrier, and the prepared copper sulfate aqueous solution (concentration of 3.0 mol / L), tetraethyl zirconium, tetraisopropyl titanate, sodium metavanadate aqueous solution (concentration of 2.0 mol / L), sodium hydroxide aqueous solution (concentration of 2.5 mol / L), and sodium carbonate aqueous solution (concentration of 2.0 mol / L) were simultaneously added to the nano-silica. The pH value of the system was strictly controlled to be 10 during the addition process. The precipitate formed by the reaction of the above four metal ions with the alkali solution was deposited on the surface of the nano-silica carrier to form a porous deposition catalyst layer. The suspension was then filtered, washed with water, and pressed into columnar porous catalyst particles with submicron graphite, coconut shell carbon powder, and adhesive (the mass ratio of the three was 3:5:2, as a supporting carrier), and then sent to a muffle furnace for treatment at 600°C for 16 hours to obtain a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst. The catalyst surface has a porous structure.

[0151] The specific surface area of ​​the catalyst is 100 m 2 / g, cylindrical, and the length of the column is 5.0mm.

[0152] The catalyst comprises 40 wt% of a support carrier, 20 wt% of a nano-silicon dioxide carrier, and 40 wt% of an active component porous deposition catalyst layer. In the active component porous deposition catalyst, according to mass percentage, copper oxide accounts for 45%, zirconium oxide accounts for 30%, titanium oxide accounts for 12.0%, and vanadium oxide accounts for 13.0%.

[0153] Comparative Preparation Example 1

[0154] This comparative preparation example provides a hydrogenation catalyst, and its preparation method is basically the same as that of Preparation Example 1, except that the raw material does not contain calcium chloride aqueous solution.

[0155] Comparative Preparation Example 2

[0156] This comparative preparation example provides a hydrogenation catalyst, and its preparation method is basically the same as that of Preparation Example 1, except that the raw material does not contain an aqueous solution of magnesium sulfate.

[0157] Comparative Preparation Example 3

[0158] This comparative preparation example provides a deposited hydrogenation catalyst, and its preparation method is basically the same as that of Preparation Example 2, except that the raw material does not contain tetraethyl zirconium.

[0159] Comparative Preparation Example 4

[0160] This comparative preparation example provides a deposited hydrogenation catalyst, and its preparation method is basically the same as that of Preparation Example 2, except that the raw material does not contain a sodium metavanadate aqueous solution.

[0161] Example 1

[0162] This embodiment provides a method for preparing methanol, which is as follows:

[0163] Taking the 500,000 tons / year CO2 hydrogenation to methanol unit as an example, the sources and quality indicators of its raw materials hydrogen and CO2 are as follows:

[0164] Hydrogen: When green power generation is used as energy to produce propylene using methanol to olefins technology (MTO process), hydrogen is a byproduct. Its quality indicators (hydrogen content and impurity content) and process parameter information are shown in Table 1:

[0165] Table 1. Hydrogen raw material indicators and process parameters

[0166]

[0167]

[0168] Carbon dioxide: The high-concentration carbon dioxide gas stream (quality indicators are shown in Table 2 below) generated during petroleum refining is recovered. First, the carbon dioxide waste gas is captured, compressed, concentrated (pressure swing adsorption PSA device), desulfurized, and denitrified to prepare a carbon dioxide raw gas with a volume content of more than 98.0%;

[0169] Table 2. Carbon dioxide raw material indicators and process parameters

[0170]

[0171] The purified carbon dioxide gas is mixed with hydrogen, then pressurized to 10.0MPa and heated to 265°C. It is transported to the inner chamber of the first-stage methanol reactor (first-stage fixed bed reactor), the mixed gas flows through the inner chamber catalyst fixed bed, and then reaches the top of the methanol reactor tower, passes through the top outer chamber homogenizer, flows evenly from top to bottom, passes through the outer chamber multi-layer catalyst fixed bed and gas homogenizer, completes the first-stage circulation process catalytic hydrogenation reaction, and the mixed gas is transported from the bottom of the outer chamber through the heat exchange and pressure reduction equipment to the first methanol phase separation device. The catalyst loaded in the above inner and outer chambers is the catalyst of Preparation Example 1. In the first-stage methanol reactor, the total residence time of the carbon dioxide and hydrogen mixed phase is ~310 seconds. The result is that the carbon dioxide conversion rate is 72.8%, and the catalytic selectivity exceeds 97.0%. .

[0172] The temperature is further reduced and refluxed in the first methanol phase separation device, and heavy components such as crude methanol and water generated by the reaction are collected from the bottom and then transported to the crude methanol intermediate tank.

[0173] The unreacted mixed gas at the top of the first methanol phase separation device is pressurized and heated (temperature raised to 180°C, pressure increased to 15.0MPa) by a compressor and a heat exchanger, and then transported to the second-stage methanol reactor (second-stage fixed bed reactor). The second-stage methanol reactor adopts the same design structure as the first-stage reactor, and the gas-liquid phase unreacted mixed gas, crude methanol, water and high-boiling point by-products are discharged from the bottom and transported to the methanol phase separation device for separation.

[0174] The mixed gas from the first and second stage methanol reactors is combined at the top of the methanol phase separation device and circulated to the second stage methanol reactor again through the compressor; the main gas volume of the top gas phase is compressed and then self-circulated at a high rate (3.6-6.0), and another small flow of mixed gas at the top is controlled and sent to the PSA hydrogen recovery device, and after concentration, it is introduced into the inlet of the secondary mixed gas circulation compressor for reuse, and part of it is sent to the tail gas incineration rate for harmless emission treatment.

[0175] The second stage methanol reactor was filled with the catalyst of Preparation Example 2. The residence time of the mixed phase in the second stage methanol reactor was 80 seconds, and the effective self-circulation ratio was 3.5 times. After the second stage methanol reactor, the cumulative conversion rate of carbon dioxide was 95.12%.

[0176] The crude methanol produced from the first and second stage methanol reactors is collected in the crude methanol storage tank and then transported to the distillation system. After two-stage distillation, refined methanol is produced from the top of the first low-pressure methanol distillation tower, and methanol, water and high-boiling point by-products are produced from the bottom. The components are heated and gasified and transported to the secondary medium-pressure distillation tower. After treatment in the secondary distillation tower, refined methanol is produced from the top, and the heavy components at the bottom are refluxed, and the reaction water is separated and sent to the water treatment device for treatment. The remaining fusel oil after dehydration is sent to the fusel oil storage tank for storage and treatment. The tail gas of the device is collected in the tail gas treatment device, and discharged after harmless treatment. The refined methanol product distilled from the two-stage distillation tower is collected in the refined methanol storage tank. Its product indicators are shown in Table 3 below:

[0177] Table 3. Methanol product indicators (GB 338-2011)

[0178]

[0179]

[0180] For the 500,000 tons / year carbon dioxide hydrogenation to methanol project in this embodiment, the carbon dioxide conversion rate is 94.88%, and the material balance data of the device are shown in Table 4 below.

[0181] Table 4. Material balance table of project process equipment

[0182]

[0183] Comparative Example 1

[0184] This comparative example provides a method for preparing methanol, which is basically the same as Example 1, except that the catalysts in the first-stage fixed bed reactor and the third-stage fixed bed reactor are replaced with the catalysts in Comparative Preparation Example 1. As a result, the cumulative conversion rate of carbon dioxide is 91.35%.

[0185] Comparative Example 2

[0186] This comparative example provides a method for preparing methanol, which is basically the same as Example 1, except that the catalysts in the first-stage fixed bed reactor and the third-stage fixed bed reactor are replaced with the catalysts in Comparative Preparation Example 2. As a result, the cumulative conversion rate of carbon dioxide is 90.82%.

[0187] Comparative Example 3

[0188] This comparative example provides a method for preparing methanol, which is basically the same as Example 1, except that the catalyst in the second-stage fixed bed reactor is replaced with the catalyst of Comparative Preparation Example 3. As a result, the cumulative conversion rate of carbon dioxide is 89.53%.

[0189] Comparative Example 4

[0190] This comparative example provides a method for preparing methanol, which is basically the same as Example 1, except that the catalyst in the second-stage fixed bed reactor is replaced with the catalyst of Comparative Preparation Example 4. As a result, the cumulative conversion rate of carbon dioxide is 88.76%.

[0191] Example 2

[0192] This embodiment provides a method for preparing green ethylene glycol, which is as follows:

[0193] The green refined methanol prepared in Example 1 is transported to the MTO unit for preparing olefins from methanol. In the MTO unit, the green refined methanol first prepares ethylene, and then the green ethylene is oxidized to prepare green ethylene oxide, and the ethylene oxide is hydrolyzed to prepare green ethylene glycol. The process of preparing green ethylene glycol from green methanol has been widely used in the methanol chemical industry. This example adopts the conventional implementation method of the chemical industry. The indicators of the green ethylene glycol finally obtained are shown in Table 5 below.

[0194] It meets the requirements of GB / T4649-2018 and the quality requirements of polyester-grade ethylene glycol raw materials. However, compared with petrochemical ethylene glycol, its ultraviolet light transmittance at 220nm and 250nm meets the national quality requirements, but is lower than that of petrochemical ethylene glycol. The reason is that the content of low molecular aldehydes, carboxylic acids and low molecular carboxylic acid esters, and alcohol by-products in this green ethylene glycol is higher than that of petrochemical ethylene glycol.

[0195] Table 5. Performance indicators of green ethylene glycol

[0196]

[0197]

[0198] Example 3

[0199] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is as follows:

[0200] The 100% green ethylene glycol prepared in the above Example 2 was used as the polyester raw material, and polymerization spinning was carried out on a 50,000 tons / year continuous polymerization melt direct spinning device.

[0201] Device capacity: 150t / d, ultra-low temperature five-reactor process design, melt direct spinning.

[0202] The purified terephthalic acid PTA and green ethylene glycol EG are prepared into slurry at a molar ratio of 1:1.135, and the prepared esterification catalyst: a mixture of zinc acetate, manganese acetate, and lithium acetate (the molar ratio of the three is 1:0.3:0.5) is injected into the slurry tank, and the total amount of esterification catalyst added is controlled to be 100ppm of PET. The injection port is designed in the slurry conveying pipeline, and the prepared composite stabilizer is injected into the slurry. The composition of the composite stabilizer is triethanolamine, sodium bisulfite, and triphenyl phosphite. Among them, the amount of triethanolamine accounts for 50ppm of the mass of PET, the amount of sodium bisulfite accounts for 20ppm of the mass of PET, and the amount of triphenyl phosphite accounts for 150ppm of the mass of PET.

[0203] After the slurry is mixed evenly, it is transported to the first esterification kettle, where a preliminary esterification reaction is carried out. The temperature of the first esterification kettle is controlled at 256-258°C, the pressure is 75KPa, and the esterification rate of the first esterification kettle is controlled at 90%-91.5%.

[0204] After the melt reaction in the first esterification kettle is completed, the second esterification kettle is introduced. The second esterification kettle is of multi-chamber design and is divided into three esterification reaction chambers. The outlet reaction temperature of the second esterification kettle is 260-262°C. The prepared nano barium sulfate tracer (barium sulfate suspension in ethylene glycol, with a mass concentration of 5% and a barium sulfate particle size of 50nm) is added from the first chamber of the second esterification kettle, and the amount added is controlled. In terms of barium sulfate, it accounts for 50ppm of the mass of PET. As a marker, the entire life cycle of the green carbon-reducing polyester can be tracked. A titanium-based multi-metal catalyst (the catalyst of Example 1 of CN117567730A) is added from the second esterification chamber, wherein the titanium element concentration is 8ppm of the mass of PET. A liquid matting agent is added to the third chamber of the second esterification kettle, and the content is 0.3% of the mass of PET.

[0205] The melt after the esterification reaction in the second esterification reactor has an esterification rate of 96.5-97.8%, which is introduced into the first prepolymerization reactor. The reaction temperature of the first prepolymerization reactor is controlled at 269-271°C and the vacuum degree is 10.0-12.0KPa. The melt after the initial polymerization reaction in the first prepolymerization reactor is introduced into the second prepolymerization reactor to further complete the prepolymerization reaction. The second prepolymerization reactor is a uniaxial disc reactor. The reaction temperature is controlled at 273-275°C and the vacuum degree is 1.0-1.3KPa. The intrinsic viscosity of the prepolymer is controlled at 0.240-0.285 (benzene Phenol: tetrachloroethane, measured in a mixed solvent of 3:2); the melt after the prepolymerization reaction is transported to the final polymerization kettle through the prepolymer delivery pump and the prepolymerization filter. The final polymerization reactor is a front and rear double-axis disc reactor, and the outlet reaction temperature is controlled at 280-282°C, and the vacuum degree is 150-175Pa; the outlet intrinsic viscosity is controlled at 0.640-0.645 (phenol: tetrachloroethane, measured in a mixed solvent of 3:2), and the melt is transported to the direct spinning workshop through the melt delivery pump to spin various specifications of green carbon-reduced polyester fibers. The process parameters are shown in Table 6 below.

[0206] Example 4

[0207] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that in Embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and the amount of the tracer barium sulfate added to the esterification two-reactor one-chamber is increased to 100 ppm.

[0208] Example 5

[0209] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that of embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and 60 ppm of 2,2,4,4-cyclohexanedicarboxylic acid is added to the pulping kettle, and 50 ppm of nano barium sulfate is also added to the second esterification kettle. All are calculated relative to the mass of PET.

[0210] Example 6

[0211] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that of embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and 80 ppm of 2,2,4,4-cyclohexanedicarboxylic acid is added to the pulping kettle, and nano barium sulfate is also added to the second esterification kettle, but the amount is 80 ppm. All are calculated relative to the mass of PET.

[0212] Example 7

[0213] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that of embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and 75 ppm of 2,2,4,4-cyclohexanedicarboxylic acid is added to the pulping kettle, and 100 ppm of sub-nano composite calcium carbonate-magnesium carbonate (including 40 ppm of calcium and 60 ppm of magnesium) is added to the second esterification kettle. All are calculated relative to the mass of PET.

[0214] Example 8

[0215] This embodiment provides a method for preparing green polyethylene terephthalate (PET), which is basically the same as that of embodiment 3, except that the process parameters are slightly different, as shown in Table 6, and 75 ppm of pentaerythritol is added to the pulping kettle, and 100 ppm of sub-nano composite calcium carbonate-magnesium carbonate (including 40 ppm of calcium and 60 ppm of magnesium) is added to the second esterification kettle. All are calculated relative to the mass of PET.

[0216] Table 6 Summary of process parameters for esterification and polymerization of carbon capture polyester

[0217]

[0218]

[0219] Comparative Example 5

[0220] The esterification and polymerization reactions are basically the same as those in Example 3, except that no esterification catalyst, tracking agent or composite stabilizer is added.

[0221] Comparative Example 5

[0222] The esterification and polymerization reactions are basically the same as those in Example 2, except that an esterification catalyst is added, and no tracking agent or composite stabilizer is added.

[0223] Comparative Example 7

[0224] The esterification and polymerization reactions are basically the same as those in Example 2, except that ethylene glycol antimony catalyst is used, and no tracer, esterification catalyst, or composite stabilizer is added.

[0225] Comparative Example 8

[0226] The polymerization monomers used are EG and PTA obtained through petrochemical process, and the esterification and polymerization reactions are basically the same as those in Example 2, except that ethylene glycol antimony catalyst is used, and no tracer, esterification catalyst or composite stabilizer is added.

[0227] The use of each additive is shown in Table 7 below.

[0228] Table 7 Summary of the use of additives in the examples

[0229]

[0230] The semi-dull PET polyester prepared in the above-mentioned embodiments and comparative examples was subjected to performance tests, as shown in Table 8 below, wherein the intrinsic viscosity was measured in a mixed solvent of phenol:tetrachloroethane, 3:2.

[0231] Table 8 Physical and chemical indicators of semi-matte PET polyester

[0232]

[0233] As can be seen from Table 8, compared with the petrochemical EG raw material (Comparative Example 8), the indicators of polyester prepared by green EG are obviously different from those of polyester prepared by petrochemical EG, mainly because the ethylene glycol produced by preparing methanol through hydrogenation of carbon dioxide has higher by-products than the petrochemical ethylene glycol. However, after adding targeted esterification catalysts and composite stabilizers, the indicators of the present invention are basically close to those of petrochemical polyester.

[0234] Through the melt direct spinning process, FDY fibers with specifications such as 83.3dtex / 144f and 55.5dtex / 72f were spun. The green carbon-reduced polyester fiber prepared with green ethylene glycol meets the market's post-application requirements and is basically the same as the polyester fiber synthesized with ethylene glycol from petrochemical methods.

[0235] Table 9 below shows the fiber indicators of 83.3dtex / 144fFDY.

[0236] Table 9 Physical and chemical indicators of 83.3dtex / 144fFDY fiber

[0237]

[0238] Table 10 below shows the quality indicators of 55.5dtex / 72f FDY fiber.

[0239] Table 10 Physical and chemical indicators of 55.5dtex / 72f FDY fiber

[0240]

[0241] The fibers are woven into fabrics, and after printing and dyeing, the fabrics are traced and tested. The test results are shown in Table 11:

[0242] Table 11 Fabric tracking test

[0243]

[0244] It can be seen that the above-mentioned tracers can be used for green tracking.

[0245] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing methanol, using carbon dioxide and hydrogen as raw materials to prepare methanol through a hydrogenation reaction, characterized in that: The hydrogenation reaction is sequentially carried out in a two-stage fixed bed reactor, the first stage fixed bed reactor comprises at least two reaction towers arranged in parallel, the second stage fixed bed reactor comprises at least one reaction tower, each reaction tower of the first stage fixed bed reactor is filled with a copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst, and each reaction tower of the second stage fixed bed reactor is filled with a copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is columnar and has a porous structure, comprising a support carrier and an active component; the active component comprises copper oxide, zinc oxide, calcium oxide, magnesium oxide and aluminum oxide; the copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst is columnar and has a porous structure, comprising a support carrier, a nano-silica carrier, and a porous deposition catalyst layer located on the surface of the nano-silica carrier, the porous deposition catalyst layer comprising copper oxide, zirconium oxide, titanium oxide and vanadium oxide; the support carrier comprises graphite, activated carbon and a binder; The copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is prepared by a preparation method comprising the following steps: 1) mixing a water-soluble zinc salt, a water-soluble magnesium salt and a water-soluble aluminum salt in the form of a solution to obtain a mixed solution; and dripping a sodium hydroxide aqueous solution into the mixed solution to obtain a coprecipitation suspension; 2) simultaneously adding a water-soluble copper salt aqueous solution, a water-soluble calcium salt aqueous solution and a sodium hydroxide aqueous solution to the coprecipitation suspension; 3) adding a sodium bicarbonate aqueous solution to adjust the pH value of the reaction system; heating and aging; 4) placing the reaction system in a high-pressure reactor, and subjecting the reaction system to high-pressure blasting, dehydration treatment, and redispersion in water to form a suspension under heating and stirring conditions; 5) adding tetrabutyl silicate dropwise to the suspension; 6) filtering, adding graphite, activated carbon and a binder to the filter cake, heating and setting, and obtaining the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst; The copper-zirconium-titanium-vanadium deposition type hydrogenation catalyst is prepared by a preparation method comprising the following steps: 1) synchronously titrating an aqueous solution of a water-soluble copper salt, tetraalkyl zirconium, tetraalkyl titanate, an aqueous solution of sodium metavanadate, an aqueous solution of sodium hydroxide and an aqueous solution of sodium carbonate on a nano-silica carrier, and forming a porous deposition catalyst layer on the nano-silica carrier after reaction; the alkyl group is a C1-6 alkyl group; 2) filtering, adding graphite, activated carbon and a binder to the filter cake, and heating treatment to obtain the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst.

2. The method for preparing methanol according to claim 1, characterized in that: The first-stage fixed bed reactor comprises 2-6 reaction towers arranged in parallel; and / or, the second-stage fixed bed reactor comprises 1-2 reaction towers.

3. The method for preparing methanol according to claim 2, characterized in that: The first-stage fixed bed reactor comprises 3-5 reaction towers arranged in parallel; and / or the second-stage fixed bed reactor comprises 2 reaction towers arranged in parallel.

4. The method for preparing methanol according to claim 2, characterized in that: In the first-stage fixed bed reactor and the second-stage fixed bed reactor, each of the parallel reaction towers is provided with a nitrogen inlet and a nitrogen outlet.

5. The method for preparing methanol according to claim 4, characterized in that: The method controls a reaction tower in the first-stage fixed bed reactor not to perform hydrogenation reaction and serves as a spare tower, and also controls a reaction tower in the second-stage fixed bed reactor not to perform hydrogenation reaction and serves as a spare tower; When the catalyst in a reaction tower of the first-stage fixed bed reactor or the second-stage fixed bed reactor performing hydrogenation reaction reaches its service life, the reaction tower is switched to a standby tower; and the reaction tower is purged with nitrogen to regenerate the catalyst, wherein the temperature of the nitrogen is 300-400°C.

6. The method for preparing methanol according to claim 1, characterized in that: Each reaction tower of the first-stage fixed bed reactor and the second-stage fixed bed reactor includes an inner chamber and an outer chamber; the inner chamber includes multiple layers of horizontally arranged tower plates; two adjacent tower plates are staggered; the outer chamber is designed as a circular tower design, and multiple groups of equalizing plates are designed at the top, middle and bottom of the outer chamber; the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is filled between the inner chamber and the equalizing plates of the outer chamber; and a filter is arranged at the bottom of the outer chamber.

7. The method for preparing methanol according to claim 6, characterized in that: The effective volumes of the inner chamber and the outer chamber are the same; and / or the residence time of the reaction gas in the inner chamber and the outer chamber is the same.

8. The method for preparing methanol according to claim 1, characterized in that: The residence time of the raw gas in the first-stage fixed bed reactor is 275-350s; and / or, after the hydrogenation reaction in the first-stage fixed bed reactor is completed, the conversion rate of carbon dioxide is 64.0%-75.8%; and / or, the volume of each reaction tower of the first-stage fixed bed reactor is 135-150m 3 The volume of the copper-zinc-calcium-magnesium-aluminum hydrogenation catalyst is 75-90m 3 .

9. The method for preparing methanol according to claim 1, characterized in that: The volume of each reaction tower of the second stage fixed bed reactor is 135-150m 3 The volume of the copper-zirconium-titanium-vanadium deposited hydrogenation catalyst is 75-90m 3 ; and / or, the residence time of the reaction system in the second-stage fixed bed reactor is 75-100s.

10. The method for preparing methanol according to claim 1, characterized in that: In the second-stage fixed-bed reactor, the effective self-circulation ratio of the reaction system is 3.5-6.0; and / or, after the hydrogenation reaction in the second-stage fixed-bed reactor is completed, the cumulative conversion rate of carbon dioxide is 92.4%-95.5%.

11. The method for preparing methanol according to claim 1, characterized in that: The temperature of the first-stage fixed bed reactor is 150-350° C., and the pressure is 5.0-20.0 MPa; and / or, the temperature of the second-stage fixed bed reactor is 120-240° C., and the pressure is 10.0-20.0 MPa.

12. The method for preparing methanol according to claim 1, characterized in that: The carbon dioxide is derived from a by-product of petroleum refining processes.

13. The method for preparing methanol according to claim 12, characterized in that: The volume content of carbon dioxide in the by-products of the petroleum refining process is 80%-90%.

14. The method for preparing methanol according to claim 12, characterized in that: The method also includes the steps of filtering, washing with water, washing with ammonia water, removing suspended solids, and treating with a pressure swing adsorption (PSA) device for the byproducts of the petroleum refining process. After these steps, the volume content of carbon dioxide is 98.0%-99.5%.

15. The method for preparing methanol according to claim 1, characterized in that: After the carbon dioxide and hydrogen are mixed and pressurized, they enter the first-stage fixed bed reactor from the bottom for hydrogenation reaction. The gas flow after the reaction flows out from the bottom of the first-stage fixed bed reactor, enters the condenser for condensation, and enters the methanol phase separation device for phase separation after decompression.

16. The method for preparing methanol according to claim 15, characterized in that: The molar ratio of carbon dioxide to hydrogen is 1:3-4.

5.

17. The method for preparing methanol according to claim 15, characterized in that: The gas flow at the top of the methanol phase separation device and the added hydrogen are mixed and pressurized, and then enter the second-stage fixed bed reactor from the lower middle part. The mixed gas flow undergoes a hydrogenation reaction in the second-stage fixed bed reactor, and the liquid component after the reaction flows out from the bottom of the second-stage fixed bed reactor and enters the methanol phase separation device for phase separation.

18. The method for preparing methanol according to claim 17, characterized in that: The amount of the added hydrogen accounts for 4%-8% of the amount of hydrogen entering the first-stage fixed bed reactor.

19. The method for preparing methanol according to claim 17, characterized in that: The tail gas at the top of the second-stage fixed bed reactor is introduced into a pressure swing adsorption (PSA) device after decompression treatment to adsorb hydrogen, and then desorb and recover the hydrogen.

20. The method for preparing methanol according to claim 19, characterized in that: The recovered hydrogen is used as the source of the additional hydrogen entering the second-stage fixed bed reactor.

21. A method for preparing ethylene glycol, comprising the steps of preparing ethylene from methanol via MTO technology, preparing ethylene oxide from ethylene oxidation, and preparing ethylene glycol from ethylene oxide hydrolysis; characterized in that: The preparation method further comprises the step of preparing methanol by using the method for preparing methanol according to any one of claims 1 to 20.

22. A method for preparing polyethylene terephthalate, comprising the steps of sequentially subjecting terephthalic acid and ethylene glycol to a first esterification, a second esterification, a first prepolymerization, a second prepolymerization and a final polymerization; characterized in that: The preparation method also includes the step of preparing ethylene glycol by the method for preparing ethylene glycol according to claim 21; the preparation method also includes the step of adding an esterification catalyst and a composite stabilizer to terephthalic acid and ethylene glycol before performing the first esterification step; the esterification catalyst is selected from a combination of one or more of zinc acetate, manganese acetate, potassium acetate, sodium acetate, cobalt acetate, calcium acetate and lithium acetate; the composite stabilizer includes an amine stabilizer, sodium bisulfite and a phosphorus stabilizer.

23. The method for preparing polyethylene terephthalate according to claim 22, characterized in that: The esterification catalyst is a mixture of zinc acetate, manganese acetate and lithium acetate; and / or, the mass of the esterification catalyst accounts for 100-200 ppm of the mass of the polyethylene terephthalate; and / or, the amine stabilizer is selected from a combination of one or more of triethanolamine, triethylamine, diethylpropylamine, tert-butylamine, and diisopropylamine; and / or, the phosphorus stabilizer is selected from a combination of one or more of triphenyl phosphite, triethyl phosphate, trimethyl phosphate, and phosphoric acid; and / or, the mass of the amine stabilizer accounts for 35-50 ppm of the mass of the polyethylene terephthalate; and / or, the mass of the sodium bisulfite accounts for 15-20 ppm of the mass of the polyethylene terephthalate; and / or, the mass of the phosphorus stabilizer accounts for 125-150 ppm of the mass of the polyethylene terephthalate.

24. The method for preparing polyethylene terephthalate according to claim 22, characterized in that: The preparation method also includes the step of adding a liquid phase tracer into terephthalic acid and ethylene glycol before the first esterification step; the liquid phase tracer is selected from a combination of one or more of isophthalic acid, phthalic acid, trimellitic acid, pyromellitic acid, cyclohexanedicarboxylic acid, 2,2,4,4-tetramethylcyclobutanedicarboxylic acid, pentaerythritol, neopentyl glycol, 1,2-dibutanol, 2,2,4,4-tetramethylcyclobutane dimethanol and 1,4-cyclohexanedimethanol; and / or, the preparation method also includes the step of adding a solid phase tracer in the second esterification step; the solid phase tracer is selected from a combination of one or more of hydrophilic nano-silica, γ-nano-aluminum oxide, nano-barium sulfate powder, sub-nano composite calcium carbonate-magnesium carbonate, sub-nano-attapulgite powder and multi-element light metal zeolite nano-powder.

Citation Information

Patent Citations

  • Nanometer supported solid-phase titanium-based multi-metal catalyst as well as preparation method and application thereof

    CN117567730A

  • Steam Reforming Of Methanol

    US20140308597A1

  • Catalysts and methods for methanol synthesis from direct hydrogenation of syngas and / or carbon dioxide

    US20190076828A1

  • Catalyst for methanol synthesis

    JP1998216522A